MyD88 is crucial for the development of a protective CNS immune response to Toxoplasma gondii infection - Torres Marbel (Journal of Neuroinflammation, 2013)
Abstract Background Toxoplasmosis is one of the most common parasitic infections in humans. It can establish chronic infection and is characterized by the formation of tissue cysts in the brain. The cysts remain largely quiescent for the life of the host, but can reactivate and cause life-threatening toxoplasmic encephalitis in immunocompromised patients, such as those with AIDS, neoplastic diseases and organ transplants. Toll-like receptor (TLR) adaptor MyD88 activation is required for the innate sensing of Toxoplasma gondii. Mice deficient in MyD88 have defective IL-12 and Th1 effector responses, and are highly susceptible to the acute phase of T. gondii infection. However, the role of this signaling pathway during cerebral infection is poorly understood and requires examination. Method MyD88-deficient mice and control mice were orally infected with T. gondii cysts. Cellular and parasite infiltration in the peripheral organs and in the brain were determined by histology and immunohistochemistry. Cytokine levels were determined by ELISA and chemokine mRNA levels were quantified by real-time PCR (qPCR). Results Thirteen days after infection, a higher parasite burden was observed but there was no histological change in the liver, heart, lungs and small intestine of MyD88−/− and MyD88+/+ mice. However, MyD88−/− mice compared to MyD88+/+ mice were highly susceptible to cerebral infection, displayed high parasite migration to the brain, severe neuropathological signs of encephalitis and succumbed within 2 weeks of oral infection. Susceptibility was primarily associated with lower expression of Th1 cytokines, especially IL-12, IFN-γ and TNF-α, significant decrease in the expression of CCL3, CCL5, CCL7 and CCL19 chemokines, marked defect of CD8+ T cells, and infiltration of CD11b+ and F4/80+ cells in the brain. Conclusion MyD88 is essential for the protection of mice during the cerebral installation of T. gondii infection. These results establish a role for MyD88 in T cell-mediated control of T. gondii in the central nervous system (CNS).